PERKEMBANGAN HUKUM ISLAM DI INDONESIA (Belanda, Jepang, dan Indonesia Merdeka sampai sekarang) - Dr. Andi Herawati, M.Ag (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
The development of Islamic law in Indonesia has been through five times with various theories. Implementation of Islamic law in the pre occupation of the Netherlands based on the theory creed; the Dutch colonial period is based on the theory Receptio in complexu and the theory Receptie; ; during the Japanese occupation happened only change the name of the institution of Islamic Courts of Priesterrad be Sooryoo Hooin, and the Court of Appeal of Hof voor Islamietsche be Kaikyoo Kootoo Hooin; at the time of independence, the effort to transform Islamic law into the rule of law; was at the time of the emergence of several reform laws and bylaws that contains the values of Islamic law.